2016
DOI: 10.1002/2016tc004126
|View full text |Cite
|
Sign up to set email alerts
|

Revised exhumation history of the Wind River Range, WY, and implications for Laramide tectonics

Abstract: A reanalysis of apatite fission track (AFT) thermochronology coupled with thermal‐kinetic modeling of samples from the Wind River Range document Late Cretaceous to early Eocene episodic cooling and exhumation of one of the largest basement‐cored ranges in the western United States. Three vertical transects taken at different latitudes along the length of the 145 km Wind River Range reveal that exhumation is uniform along strike suggesting steady displacement along the Wind River Fault, and significant exhumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 61 publications
2
36
2
Order By: Relevance
“…Previous studies of uplift, basin subsidence, and erosional histories of the Laramide in Wyoming indicate mostly early Cenozoic ages (e.g., Peyton et al, ; Stevens et al, ); these relatively young ages may represent thermal processes related to westward roll‐back of the subducting slab (Fan & Carrapa, ) or accretion of Shatsky conjugate depleted mantle lithosphere beneath Wyoming and the associated upper crustal deformation and subsequent removal (Humphreys et al, ; Stevens et al, ). Westward to southwestward migration of magmatism in the mid‐Cenozoic is consistent with the history of the stress field (Bird, ) and can be explained by westward migration of the Farallon plate hingeline and falling away of the slab (referred to as slab rollback ; Best et al, ; Coney & Reynolds, ; Constenius, ; Dickinson & Snyder, ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies of uplift, basin subsidence, and erosional histories of the Laramide in Wyoming indicate mostly early Cenozoic ages (e.g., Peyton et al, ; Stevens et al, ); these relatively young ages may represent thermal processes related to westward roll‐back of the subducting slab (Fan & Carrapa, ) or accretion of Shatsky conjugate depleted mantle lithosphere beneath Wyoming and the associated upper crustal deformation and subsequent removal (Humphreys et al, ; Stevens et al, ). Westward to southwestward migration of magmatism in the mid‐Cenozoic is consistent with the history of the stress field (Bird, ) and can be explained by westward migration of the Farallon plate hingeline and falling away of the slab (referred to as slab rollback ; Best et al, ; Coney & Reynolds, ; Constenius, ; Dickinson & Snyder, ).…”
Section: Discussionmentioning
confidence: 98%
“…However, the Laramide uplifts of Montana present some difficulties for recent geodynamic models that project a narrow zone of shallow flat-slab subduction from the Mojave Desert region into central Wyoming along a northnortheastward trajectory (e.g., Axen et al, 2018;Jones et al, 2011;. Refined models might include the effects of a spatially less restricted Shatsky conjugate moving along a trajectory more eastward than northward; a zone of somewhat deeper, but still flat, subducting Farallon lithosphere to the north of the zone of shallowest subduction (e.g., Saleeby, 2003); and a cratonic lithospheric root that extends farther north below the Archean crust of western Journal of Geophysical Research: Solid Earth may represent thermal processes related to westward roll-back of the subducting slab (Fan & Carrapa, 2014) or accretion of Shatsky conjugate depleted mantle lithosphere beneath Wyoming and the associated upper crustal deformation and subsequent removal (Humphreys et al, 2015;Stevens et al, 2016). Westward to southwestward migration of magmatism in the mid-Cenozoic is consistent with the history of the stress field (Bird, 2002) and can be explained by westward migration of the Farallon plate hingeline and falling away of the slab (referred to as slab rollback; Best et al, 2009;Coney & Reynolds, 1977;Constenius, 1996;Dickinson & Snyder, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AFT ages are similar to AFT ages reported by Grujic et al [] from Bhutan but significantly older than ages reported by Adlakha et al []. We note that Adlakha et al [] used a slow etching protocol for AFT, which has been shown to produce unreliable ages [e.g., Murrell et al ., ; Stevens et al ., ].…”
Section: Exhumation Historymentioning
confidence: 99%